A Centenary Portrait - Amarante, Dirce Waltrick do (ABEI Journal, 2016)
This article is about the quite turbulent editing history of A Portrait of the Artist as a Young Man and the importance of Harriet Weaver as Joyce’seditor. It also points out some characteristics of this novel, such as the presence of epiphanies.Keywords: Harriet Weaver, epiphanies, English language, Catholic church.